Low-tech serious games in higher education: bridging the digital divide and enhancing student thinking and performance - Chong-Wen Chen (Humanities & Social Sciences Communications)
Abstract Serious games in education are often tied to digital learning environments, which require complex gamified content and systems to enhance students’ motivation. However, such digital-focused approaches risk widening the digital divide and may lead to digital addiction. Additionally, games rooted in behaviorism may not meaningfully improve student performance. This paper argues that inquiry-based methods can better engage college students by stimulating their thinking and enhancing learning outcomes in natural, playful settings without relying on advanced digital infrastructure. Through a case study of low-tech serious games in a theory-based and interdisciplinary course in design, this paper demonstrates that hands-on and experiential learning tasks foster a deeper comprehension of the subject matter, bringing significant performance improvements compared to traditional lecture-based instruction. Encouraging critical thinking before introducing new concepts is central to this approach. However, spurring such thinking can also introduce the risk of knowledge confusion, highlighting the need for regular reviews or assignments to mitigate this issue in future implementations. The proposed games are simple to execute and replicate, requiring minimal technical resources. This paper suggests that serious game design for theory courses in higher education can be effectively carried out in low-tech settings, avoiding the deepening of the digital divide while contributing to the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 10 (Reduced Inequality).